2017
DOI: 10.1017/s2045796016001220
|View full text |Cite
|
Sign up to set email alerts
|

Hysterectomy and incidence of depressive symptoms in midlife women: the Australian Longitudinal Study on Women's Health

Abstract: Women with a hysterectomy (with and without bilateral oophorectomy) have a higher risk of new incidence of depressive symptoms in the longer term that was not explained by lifestyle or socio-economic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 36 publications
2
36
0
4
Order By: Relevance
“…6 However, results from a small survey in Australia showed substantial variation between practitioners' views on the age they would routinely recommend removal of both ovaries at the time of hysterectomy for benign indications, with 50% recommending removal at age 55 years. 7 Our previous research has shown associations between hysterectomy (with and without bilateral oophorectomy) and poorer physical 8 and mental 9 health. Hysterectomy has also been associated with chronic diseases such as diabetes, 10 stroke, 11 and certain cancers.…”
Section: Introductionmentioning
confidence: 98%
“…6 However, results from a small survey in Australia showed substantial variation between practitioners' views on the age they would routinely recommend removal of both ovaries at the time of hysterectomy for benign indications, with 50% recommending removal at age 55 years. 7 Our previous research has shown associations between hysterectomy (with and without bilateral oophorectomy) and poorer physical 8 and mental 9 health. Hysterectomy has also been associated with chronic diseases such as diabetes, 10 stroke, 11 and certain cancers.…”
Section: Introductionmentioning
confidence: 98%
“…The same findings were observed for the comorbidities. Our findings and the results of another study [ 12 ] suggest that once a hysterectomy is performed on a woman, early-premenopausal hormone therapy might not be beneficial for improving her psychological health.…”
Section: Discussionmentioning
confidence: 51%
“…These operations had a joint effect on the increased risk of depression. Although ovarian conservation at hysterectomy might be beneficial for a lowering the risk of developing subsequent depression, the results of ours and other studies revealed that both women underwent a hysterectomy with ovarian conservation and those underwent a hysterectomy with oophorectomy would have an increased risk of depression [ 12 , 14 ]. The results imply that hysterectomy itself would be a predisposing factor for developing depression, with or without oophorectomy.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Some studies have examined the association between depression and hysterectomy with or without oophorectomy, obtaining mixed results [70,71,72,73]. A study by the Australian Longitudinal Study on Women’s Health, which enrolled 5336 women, detected an elevated risk of depressive symptoms, 20% higher in women with hysterectomy and ovarian conservation and 44% higher in women with hysterectomy without ovarian conservation compared to controls (women without hysterectomy) [74].…”
Section: The Influence Of Menopausal Transition and Menopause Hormmentioning
confidence: 99%